Ensino de inglês para crianças: o fator idade no ensino-aprendizagem da língua e suas especificidades - Passarella, Letícia Aparecida (2016)
The interest in English Teaching for Young Learners has increased in the past two decades. This rising interest is many times justified by the moto “the sooner you learn another language, the better”. Bearing this in mind, this study aims at understanding whether age is the main factor for the success of English learning in childhood. In order to attain this aim, bibliographic research was carried out so as to comprehend what is claimed by researchers in academic studies about this topic. Thus, a historical overview of English language teaching is presented, as well as the methodological paths taken over time in this country. Moreover, this paper sets out to understand more deeply theoretical studies about aspects regarding English teaching for children and, consequently, reflect on some studies that address the same academic field. It was concluded that age is one among several factors to be taken into account when teaching a foreign language to children. However, it cannot be considered as the only factor for successful learning. Those who work with teaching English to children should keep in mind that the establishment of a secure environment, the concern with affectionateness and playfulness are also very important when learning a modern foreign language at childhood